How useful are experiential learning models in framing the implementation of government policy for international development? A case study of DFID’s GTF Programme - Wilkinson, Edith (Unpublished, 2017)
This paper examines experiential learning theory and its impact on the design, implementation and evaluation of learning beyond the level of the individual. The existence of experiential learning frameworks at organization and society levels will be reviewed, ‘Kolb-inspired’ models will be investigated and their application will be discussed. In doing so, the paper aims to identify learning processes that take experience into account and that are applicable at organisational and interorganisational level. The approach adopted in this paper is, firstly, to lay out theoretical foundations for embedding experience in a process of learning and, secondly, to confront them with empirical insights from an international development policy initiative. The UK government’s Department for International Development (DFID) fund for Governance and Transparency provides an ideal testbed to investigate the suitability of making use of such experiential learning frameworks in the international development context. The paper will contribute to wider discussion by suggesting that policy implementation and international development programming could gain valuable insight from exploring the suitability of experiential learning frameworks.
Keywords: Experiential learning; international development; governance; resilience